(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The purpose of the present study was to assess the clinical and radiological outcome following repair of furcal perforation by mineral trioxide aggregate (MTA) and intermediate restorative material (IRM) in mandibular molar teeth. Forty teeth having furcal perforation were enrolled in this study, out of which 20 teeth were treated with MTA and the remaining 20 teeth were subjected to IRM treatment. Following perforation repair, all teeth were subjected to root canal treatment followed by final restoration. Clinical and radiological outcome was evaluated at 3, 6 and 12 months interval. The results showed that in both MTA and IRM groups, pain, tenderness on percussion as well as swelling and sinus was gradually decreased with the increase of the observation period. Furthermore, the widening of the periodontal ligament space and communi-cation with the oral cavity were gradually decreased. Although there was no significant differences between MTA and IRM at 3 and 6 months observation period but at 12 months, the clinical outcome between MTA and IRM was statistically significant (p<0.05). It can be concluded that repair of furcal perforation by MTA showed more effective than that of IRM.